Immune checkpoint inhibitors for the treatment of Tiple-negative breast cancer - Shao, Yizhe; Yang, Chenziqiu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Recently, the use of immune checkpoint inhibitors (ICIs) on triple negative breast cancer have been a hot research topic. immune checkpoints are vital as they prevent an immune response from being so strong that it kills healthy cells, which is unwanted. When T cell surface proteins bind to partner proteins (immune checkpoint proteins) on other cells, for instance tumor cells, immune checkpoints engage. When the checkpoint and immune checkpoint protein bind together, a signal is released to prevent the cancer from being killed by the immune system. ICIs work by stopping checkpoint proteins from binding with partner proteins, so the “off” signal was not sent, allowing the immune system to kill the cancer cells. In this review we will focus of the effect of ICI monotherapy, ICI with chemotherapy and ICI with radiotherapy. Results showed that ICI monotherapy, combination of ICIs and chemotherapy, and combination of ICI and radiotherapy have greatly improved ORR, PIS, and OS compared to the traditional chemotherapy. The combination therapy have also revealed a higher cost-effectiveness compared to ICI monotherapy.